De um regime a outro: perspectivas e diálogos do cinema em Deleuze e Rancière - Sousa Junior, Maurício José de (2021)
This thesis seeks to understand the aesthetics related to cinema in the different perspectives of two authors: Gilles Deleuze and Jacques Rancière. Trying to identify the phenomena of this art according to the looks of each, we reflect on a non-representative thought for cinematographic interpretations in their relationship with history. We understand that this interdisciplinary effort goes beyond the dissection of differences and anchors its bases in the communication of a sensitive. We intend to experience the research of these theoretical bodies involving us in the intense movement of passage that transcribes their marks from one regime of visibility from art to another. This journey during, small links are communicated. Immersed in the specificity of cinema images, we adopt a metaporal metod to understand how they can help to think the elements of an anti-representation in the analysis of films.